Análise numérica de nanoantena dipolo-espira de banda larga - LOPES, Patrik Coelho (2019)
This work has as objective to analyze numerically the combination of broadband dipole-loop plasmonics nanoantennas. The numerical analysis is done by software Comsol, where are investigated the bandwidth, the input impedance, the reflection coefficient, the electric field distribution, and the gain radiation diagram. It is shown, in the results, that the dipole-loop antenna can have a bandwidth of up to 64.98%.